TINJAUAN YURIDIS TERHADAP KEPATUTAN PERUSAHAAN DALAM MELAKSANAKAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN - Darmi wati (Fakultas Hukum Universitas Islam Indragiri, 2017)
Decency is the Company's policy, which is tailored to the financial capabilities of the Company, and the potential risks that lead to social and environmental responsibility should be borne by Perseroa in accordance with its business activities without prejudice to the obligations under the laws and regulations related to the Company's business activities. The forms of sanctions that can be given to companies that do not implement the Social and Environmental Responsibility Company are administrative sanctions such as written warnings, restrictions on business activities, freezing, or revocation of business activities and / or facility